Bringing the field into the classroom: an innovative methodology in global health teaching - Dr. M H Bryant, MBBS; J Wolff, MD (Elsevier, 2015)
Background: The practice of global health is difficult to teach from a US-based classroom. Students benefit from experiencing how theory becomes practice in the chaotic environments of under-resourced health programmes in developing countries. We could not take our students to the field during weekly course work, so we designed a course to bring the field to the students. We created innovative partnerships with locally based organisations that implement programmes in developing countries. Each student works with the same organisation for 4 months to resolve organisational challenges in human resource, quality, information, logistics, or financial management. Methods: We sent an online survey to 150 students on completion of the course, asking students to rate the course on a 5-point Likert scale. The survey included questions in the categories of knowledge and skill development, relevance and value of materials, integration of learning, and the degree to which the course had prepared them for their career. We received 102 responses (68%) which were analysed and compared with other methods of teaching. We used Nvivo to analyse 850 bi-weekly student reflections and grounded theory was used to identify themes. Findings: Students consistently ranked the course highly in all categories (mean 4·87, median 4·91, range 4·16-5·00), and scored the course significantly higher than other courses teaching similar materials in the same or in other departments. These findings were not affected by the ratings of individual teachers. Qualitative analysis showed that students reported the teaching approach as: challenging but rewarding, effective in developing new skills, and successful in drawing together all aspects of their previous learning. Students consistently identified working with organisations in Africa, Asia, or Latin America, and solving their real challenges as the most important aspect of the course. All respondents would recommend the course to other students. Informal questioning of the partner organisations indicated that the work of the students was helpful and 50-75% of products by students were implemented. Interpretation: The teaching method created for this course is effective in building practical skills. Students found this method to be better than more established approaches such as case studies, classroom simulations, and discussions. Our findings suggest that to better prepare students to work in global health we should engage more closely with actual implementers and reduce reliance on lecture and case-study methodologies. Funding: None.